THE EFFECT OF SINGULER FINITE ELEMENT ON THE STRESS INTENSITY FACTORS CALCULATED WITH THE FINITE ELEMENT METHODS IN A PRE-STRECHED STRIP WITH A CRACK - Turan, Arzu (YILDIZ TECHNICAL UNIV, 2005)
In this work, the effect of singular finite elements on the stress intensity factors (SIF) calculated with the Finite Element Methods (FEM) in a pre-stressed strip with a crack is investigated. It is known that in the determination of the SIF by the use of displacements, the singular finite elements should be employed. As a result of this the difficulties arise from the FEM modeling. However, determination of SIF by employing one of the Energy Methods such as Energy Release Rate, the requirement for the use of singular finite elements in the FEM modeling at the around of crack is not precise. So, in this work it is shown that, with a concrete problem as an example, the use of the singular finite elements under calculation of SIF through Energy Release Rate Method is unnecessary.
Keywords: Stress intensity factors; Finite element methods; Singular finite element; Composite; Crack; Initial stres; Engineering